Procesos de diferenciación de personas de nacionalidad extranjera desde la normativa sobre empleo de hogar. El caso de las empleadas de hogar de nacionalidad extranjera extracomunitaria en España - López Fernández, Rosalía; Maroto Blanco, José Manuel (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
The aim of this text is to analyse the differentiation processes and mechanisms of foreign population, specifically migrant women of non - European Union foreign nationality, which are produced by the legislation on domestic employment. From the life stories of fifteen women it will be addressed how the practices and social representations generated in the legislation itself build ethnically and occupationally degraded subjects. These women are represented as a feminized, homogenous and as an inferiorized collective, whilst in the area of domestic work converge different axis of oppression that are not amended by legislation. This analysis will show that although many of these differentiation processes are interconnected with elements of a structural nature, the naturalization of inequality is elaborated from concrete practices that are not only exhausted in the normative.